Pelatihan Intentional Change Model untuk Meningkatkan Leader Effectiveness Pengurus PPGT - Ellyana Surya Mahari; Seger Handoyo; Maria Eko (Humanitas (Jurnal Psikologi), 2020)
The effectiveness of the leader is not easy to achieve by a leader. The leader must build awareness to equip himself and his members for the achievement of objectives. Intrapersonal beliefs in their capabilities to function as leaders are called leader role-efficacy (LRE), their ability to navigate and manage interpersonal relationships with their members is called leader trust in subordinate (LTS), both of which are key elements of leader effectiveness. This study aims to find out whether intentional change model (ICM) training can improve the leader effectiveness of PPGT administrators in the Pajalesang Palopo congregation. The subject of the research was the management of PPGT organization with fifteen people as one group pre and post-test design. The pre-test questionnaire was given a week before treatment and the post-test questionnaire was given two weeks after treatment. Measuring instruments used by researchers are the Leader effectiveness scale from Ladegard and Gjerde (2014) and Psychological Capital Questionnaire (PCQ) from Luthans, Youssef, and Avolio (2015). From the measurements using the t sample t-test analysis technique, it was found that there were significant differences in the values before and after being treated with Intentional change model training with a significance value of p = 0,000 (p?0.05). Keywords: Leader effectiveness; Intentional Change Model; PPGT.